KESULITAN BELAJAR SISWA PADA PEMBELAJARAN BIOLOGI MATERI EKOSISTEM BERDASARKAN PENGGUNAAN STRATEGI PEMBELAJARAN - Apriani, Isna Nur; Sudrajat, Ahmad Kamal (Jurnal Edukasi Biologi, 2025)
This study aims to identify students' learning difficulties in ecosystem materials based on differences in learning strategies and factors causing learning difficulties, and to describe the efforts made by students and teachers to overcome these learning difficulties. This study was conducted at SMA Negeri 1 Bantul from February to May 2025. The method used in this study was a combination of descriptive, quantitative and qualitative methods. Data collection was carried out through questionnaires, interviews, and documentation. The results of the study showed that students experienced fewer learning difficulties in the Discovery Learning (DL) strategy compared to the Project-based Learning (PjBL) strategy. The factor causing learning difficulties in the Discovery Learning (DL) strategy was low student interest in learning, whereas the cause in the Project-based Learning (PBL) strategy was the numerous community activities in which students participated and the teacher's lack of readiness. The efforts made by students included dividing tasks into groups and utilising additional learning resources, while teachers played a role in providing scaffolding and extending the project's duration. These findings suggest that the selection of learning strategies should consider the characteristics and readiness of students to learn.